Redox-Polymer-Wired [NiFeSe] Hydrogenase Variants with Enhanced O2 Stability for Triple-Protected High-Current-Density H2-Oxidation Bioanodes - Ruff, Adrian (2020)
Variants of the highly active [NiFeSe] hydrogenase from D. vulgaris Hildenborough that exhibit enhanced O2 tolerance were used as H2-oxidation catalysts in H2/O2 biofuel cells. Two [NiFeSe] variants were electrically wired by means of low-potential viologen-modified redox polymers and evaluated with respect to H2-oxidation and stability against O2 in the immobilized state. The two variants showed maximum current densities of (450±84) μA cm−2 for G491A and (476±172) μA cm−2 for variant G941S on glassy carbon electrodes and a higher O2 tolerance than the wild type. In addition, the polymer protected the enzyme from O2 damage and high-potential inactivation, establishing a triple protection for the bioanode. The use of gas-diffusion bioanodes provided current densities for H2-oxidation of up to 6.3 mA cm−2. Combination of the gas-diffusion bioanode with a bilirubin oxidase-based gas-diffusion O2-reducing biocathode in a membrane-free biofuel cell under anode-limiting conditions showed unprecedented benchmark power densities of 4.4 mW cm−2 at 0.7 V and an open-circuit voltage of 1.14 V even at moderate catalyst loadings, outperforming the previously reported system obtained with the [NiFeSe] wild type and the [NiFe] hydrogenase from D. vulgaris Miyazaki F.